A review of recent progress on directional metasurfaces: concept, design, and application. (22nd September 2022) - Chen, Ke; Feng, Yijun
Abstract: Metasurfaces have provided a new paradigm to control electromagnetic waves by manipulating the spatially varying distribution of subwavelength artificial structures across the interface. Directional metasurfaces, a kind of metasurface with direction-dependent properties, possess different wave functionalities upon the incidence wave coming from opposite directions. The diversified wave-manipulation capabilities of directional metasurfaces show advantages of compactness, flatness, scalability, direction-dependence, etc, exhibiting promising potentials for a plethora of applications. Here, we present a review on the recent progress of directional metasurfaces, including the concept origin, the practical realization of meta-structures, the design method for direction-dependent wavefront tailoring, and the application aspects of directional metasurfaces. In the conclusion, we present possible further research directions in this field based on our own perspectives.